Effect of Chinese Herbal Medicine Mixture 919 Syrup on Regulation of the Ghrelin Pathway and Intestinal Microbiota in Rats With Non-alcoholic Fatty Liver Disease - Chen, Manman; Xing, Jingwei; Pan, Danqing; Gao, Pengfei (Frontiers in Microbiology, 2021)
As a manifestation of metabolic syndrome in the liver, non-alcoholic fatty liver disease (NAFLD) has become the top cause of liver disease in many countries. Recent studies have shown that intestinal microbiota disorder plays an important role in the occurrence and development of NAFLD and that regulating intestinal microbiota provides a new option for NAFLD treatment. In addition, research indicates that risk of NAFLD increases as body mass index rises, and interventions that reduce body weight and change diet can help to lower the incidence of NAFLD. Studies have found that 919 syrup may effectively treat NAFLD in rats by improving liver function and lipid metabolism and regulating body weight and feed intake, however its potential toxicity and the specific mechanism by which it controls this disease require further exploration. This study assesses both the toxicity of 919 syrup and its regulatory effect on the appetite-related Ghrelin pathway and intestinal microbiota of rats with NAFLD. Results indicate that 919 syrup has no obvious side-effects on body weight, feed intake, blood glucose level, hepatorenal function, and liver tissue structure of normal rats. Moreover, 919 syrup can reverse abnormal changes to expression of Ghrelin pathway genes related to appetite in both the brain and stomach and repair alterations to the intestinal microbiota in rats with NAFLD. This herbal medicine is a safe and promising therapeutic drug for the treatment of NAFLD.